The Effects of Granulocyte Colony Stimulating Factor on Candidial Sepsis in Neutropenic Neonates - Mutlu, Mehmet; Aslan, Yakup (Fırat University, 2002)
Aim: This study was carried out to evaluate the effects of granulocyte colony stimulating factor (G-CSF) therapy on candidial sepsis in neutropenic neonates. Material and Method: The prospective, double-blind, randomized and placebo controlled trial was performed on 31 neutropenic neonates with candidial sepsis administered G-CSF in 16 infants (group I) or placebo in 15 infants (group II). G-CSF therapy (5 µ g/kg/day, for 5 days) or placebo was administered as soon as the initial sepsis findings appeared. Liposomal-amphotericin B (L-AMB) treatment was started when candida determined in blood culture. Score for neonatal acute physiology (SNAP) was calculated at the beginning of the study. Töllner's sepsis score, complete blood counts, absolute neutrophil count (ANC), lymphocyte, monocyte and eosinophil counts, immature to total neutrophil ratio (I/T) were performed or calculated on the 0 to to 5, 7, 10, 14, 21th days. Results: Mean gestational mean birth weights, mean postnatal ages at the diagnosis of intection age of group I and II were similar. The prematurity rate was 94% in group I and 93% in group II. At the beginning of the study; Töllner's sepsis score, SNAP, ANC and APR levels were similar in both groups. However, increase in ANC, decrease of sepsis score and APR were significantly higher in group I than group II. The periods of clinical improvement, the duration of L-AMB therapy and hospitalization for infection significantly shorter and the cumulative dose of L-AMB was significantly lower in group I than group II. Although the mortality rate was lower in group I than group II, albeit difference was not significant. No adverse effects of G-CSF were noted, but hipokalemia related to L-AMB was observed only in one patient. Conclusion: It was concluded that the administration of G-CSF plus to antifungal agents in neutropenic neonates with candidial sepsis is safe and reliable.

Amaç: Bu çalışma nötropenik yenidoğan candida sepsisinde granülosit koloni uyarıcı faktör (G-CSF) tedavisinin etkilerini incelemek amacı ile gerçekleştirildi. Gereç ve Yöntem: Bu prospektif, çift kör, plasebo kotrollü çalışma yenidoğan ünitemizde kanıtlanmış candida sepsisi tanısı ile tedavi edilen 16'sı G-CSF (çalışma grubu) ve 15'i plasebo (kontrol grubu) alan toplam 31 nötropenik yenidoğanda rasgele örnekleme yöntemi ile gerçekleştirildi. Vakalara, klinik sepsis tanısı konulduğu anda G-CSF (5 µg/kg/ gün, 5 gün) veya plasebo, kan kültüründe candida ürediğinde ise lipozomal amfoterisin-B (L-AMB) tedavisi başlandı. Bütün vakalarda yenidoğanın akut fizyolojik skoru (YAFS) başlangıçta bir kez; Töllner sepsis skoru, tam kan sayımı, mutlak nötrofil sayısı (MNS), lenfosit, monosit ve eozinofil sayıları ve immatür/total nötrofil (I/T) oranı 0-5, 7, 10, 14. günlerde ve daha sonra haftalık aralarla çalışıldı. Bulgular: Çalışma ve kontrol grubunun ortalama gestasyon yaşları aralarında istatistiksel farklılık yoktu. Çalışma grubunda yer alan vakaların %94'ü ve plasebo grubundakilerin %93'ü preterm idi. Tanı anında belirlenen sepsis skoru, YAFS, MNS ve AFR düzeyleri gruplar arasında istatistiksel olarak farksız olmasına karşın, G-CSF grubunda plasebo grubuna göre MNS'nin anlamlı derecede arttığı, sepsis skorlarının daha erken düştüğü, AFR'nın daha erken negatifleştiği, klinik bulguların düzelme süresi, L-AMB ile tedavi süresi ve enfeksiyon nedeni ile yatış süresi'nin daha kısa, kümülatif L-AMB dozunun ve mortalite oranlarının daha düşük olduğu (sırası ile %19 ve %47) gözlendi. G-CSF tedavisine bağlı yan etki gözlenmez iken, L-AMB tedavisine bağlı olarak bir vakada hipokalemi gelişti. Sonuç: Sonuç olarak, nötropenik yenidoğan candida sepsislerinde destek tedavisi olarak G-CSF uygulamasının yararlı ve güvenilir olduğu kanısına varıldı.
NÖTROPENİK YENİDOĞAN CANDİDA SEPSİSLERİNDE GRANÜLOSİT KOLONİ UYARICI FAKTÖR TEDAVİSİNİN ETKİLERİ